Competitive position of Bangladesh and China in the global clothing export market: An analysis of revealed comparative advantage - ATM Adnan; Ayub Nabi Khan; Md. Shahidul Islam (Trends Economics and Management, 2019)
Purpose of the article: The Ready-Made Garment (RMG) industry remains the most crucial segment of Bangladesh's economy besides the agricultural sector in terms of foreign currency earning via export and employment generation. Several international studies predict that Bangladesh will be the next apparel sourcing hotspot after China due to the availability of reasonably priced labour force and other factors of production. This paper intends to exhibits the relative competitive position of China and Bangladesh for the ready-made garment industry in the global made-up clothing market and how its pattern has changed over the period of 2001-2017. Methodology/methods: Balassa's RCA indices have been used to calculate for all the 34 product groups under HS 61 and HS 62 for up to four digits level of the study period of 2001 to 2017 of both countries. Descriptive statistical techniques have been applied to reveal the sustainability and predictability of the comparative advantage of both countries. Scientific aim: The findings of the study would be beneficial for the policy-makers and researchers in developing export promotion policies for generating industry competitiveness considering the valuable factors of both countries such as factors of production and geological position. Findings: The analysis has revealed that Bangladesh has achieved a significant comparative advantage over China in 26 product categories out of 34 product categories in 2017, whereas China has able to gain the RCA on only 8 product groups in the same study period. The findings also reveal that although Bangladesh has achieved significant RCA in most of the product types, its volatility remains on the higher side. Conclusion: This paper is one of the trivial pursuits to perform an organized analysis of revealed comparative advantage of Bangladesh and China on clothing (RMG) trade to major global markets.
Keywords: F14; L60; 650; ready-made garments industry; export; revealed comparative advantage; Bangladesh; China